Mass transfer performance of 2-amino-2-methyl-1-propanol and piperazine promoted 2-amino-2-methyl-1-propanol blended solvent in high pressure CO2 absorption - Hairul, N.A.H. (Elsevier Ltd, 2016)
This paper reports the absorption performance study for 2-amino-2-methyl-1-propanol (AMP) and piperazine (PZ) promoted AMP (PZ + AMP) blend for the removal of CO2 from CO2 rich-natural gas (NG) at high pressure conditions. The absorption experiments were conducted in a high pressure bench-scale absorption column packed with Sulzer metal gauze packing. The effects of PZ concentration (3-9 wt), liquid flow rate (2.89 to 4.33 m3/m2 h), and CO2 concentration in NG (30-50) on the mass transfer performance were evaluated in terms of CO2 removal efficiency () and overall volumetric mass transfer coefficient based on partial pressure driving force (KGav). In addition, the effect of various operating pressures (0.1-5.0 MPa) has also been evaluated in terms of the overall volumetric mass transfer coefficient based on unit mol fraction (Kyav). The results in this study have shown that, the mass transfer performance of PZ + AMP blended solvent is better than that of the single AMP solvent. The value of KGav increases with increasing PZ concentration and liquid flow rate. However, this value decreases with increasing CO2 concentration in NG. Other than that, the process performance can be increased by increasing the operating pressure, with a significant increase in the Kyav value which can be observed at operating pressures of higher than 2.0 MPa. Â© 2016 Elsevier Ltd.